Effect of an activity wristband-based intermittent teaching unit in Physical Education on studentsʼ physical activity and its psychological mediators: a cluster-randomized controlled trial. School-fit study - Guijarro-Romero, Santiago; Mayorga-Vega, Daniel; Casado-Robles, Carolina; Viciana, Jesús (Frontiers in Psychology, 2023)
Objective The main objective of the present study was to examine the effects of an intermittent teaching unit based on the use of activity wristbands and behavior modification strategies on high school studentsʼ perceptions of autonomy support, satisfaction of basic psychological needs, motivation toward Physical Education and physical activity, intention to be physically active, and habitual physical activity levels. Materials and methods An initial sample of 353 high school students (final sample = 175; 45.7% females; mean age = 13.3 ± 1.2 years) from two public high schools were cluster-randomly assigned into the intermittent (IG, n = 100) and control (CG, n = 75) groups. The IG performed an intermittent teaching unit twice a week for eight weeks. Specifically, the last 15 min of each lesson were used. As the main strategy to promote the practice of regular physical activity, students wore an activity wristband the whole day during the intervention period. Additionally, other behavior modification strategies were also applied (e.g., educational counseling, physical activity goals or reminders). Regarding the CG, during the intervention period (i.e,, the eight weeks that took place the intermittent teaching unit) they also performed two Physical Education sessions, but without using activity wristbands or other behavior modification strategies. Before and after the intervention, as well as at the end of the follow-up period (six weeks), students’ physical activity practice mediators and physical activity levels were measured by validated questionnaires. Results The Multilevel Linear Model results showed that the IG students statistically significantly improved cognitive and procedural autonomy support from pre- to post-intervention (p < 0.05). They also statistically significantly improved autonomy and relatedness basic psychological needs, and autonomous motivation toward physical activity scores from post-intervention to follow-up (p < 0.05). Moreover, the results showed that the IG students statistically significantly improved habitual physical activity scores from pre- to post-intervention, and from post-intervention to follow-up (p < 0.05). Conclusion The intermittent teaching unit based on the use of activity wristbands and other behavior modification strategies was effective for improving studentsʼ autonomy support and habitual physical activity levels, but not the rest of physical activity practice mediators. Clinical trial registration https://register.clinicaltrials.gov/, ID: NCT05949463.